Public Health Measures and SARS-CoV-2 Cases in the Juvenile Justice System: Implications for Pandemic Response in the Detention Setting. Issue 2 (February 2023) - Davidson, Asha; Aggarwal, Shelley; Eissa, Mona; Benjamins, Laura; Will, John; Beyda, Rebecca
Abstract : Detained youth are a historically vulnerable population, housed in a setting that is challenging to infection control during disease outbreaks. There are limited data or discussion in the literature about coronavirus disease 2019 in the juvenile justice setting. This article evaluates and reflects upon the case positivity of severe acute respiratory syndrome-coronavirus-2 in two large, urban juvenile justice centers in cities with differing local public health measures and community positivity rates. Abstract: Objective: The purpose of this study was to examine severe acute respiratory syndrome-coronavirus-2 case positivity in juvenile justice facilities of two different states alongside institutional, local, and state public health policies during the first 6 months of the coronavirus disease 2019 pandemic. Methods: This retrospective chart review examined two large, urban juvenile justice centers in California and Texas. Positive intake or day 12 tests were considered suggestive of community-acquired severe acute respiratory syndrome-coronavirus-2 infection. Researchers examined state and county restrictions, closings, and openings. The study included all of the youths 10 to 18 years residing in the facilities between March and August 2020. The main outcomes measured case positivity in each facility and compared it with community positivity rates and state public health measures. Results: In total, 530 youth were included (Texas, n = 319; California, n = 211). The Texas facility reported a higher number of positive cases (24) versus the California facility (3) ( P < 0.05). Of the positive youth, 70% were asymptomatic, and none required hospitalization. Intake and day 12 tests were positive in <1% of California youth compared with a rate of 4% in Texas ( P < 0.05). California and Texas instituted mask mandates in May and July 2020, respectively. California restricted indoor capacity until August, but Texas varied from 25% to 75% capacity through July. Conclusions: The Texas facility reported a higher percentage of community-acquired infections compared with California, coinciding with reopening measures in Texas. Texas also enacted a mask mandate later than California. These public health measures, among other factors, likely contributed to higher community rates in Texas, thereby affecting rates among the detained youth.